Comparison study of rugosity modelling resulting from fledermaus, benthic terrain modeler and coral detection model derived from algorithm topographic position index / Muhammad Afiq Rosli - Rosli, Muhammad Afiq (2019)
Sea coral reefs are very important and crucial for marine life especially fish as it is their habitat and source o f food. The main purpose o f this study is to create the automated tool in ArcGlS toolbox which is to identify the coral reefs around Pulau Bidong, Terengganu. The data from multibeam will be processed by insert value the sound velocity profile (SVP), insert tide value and patch test calibration value filtered using QPS Qimera, then get the bathymetry profile. While QPS Fledermaus that will produee by compute rugosity. Rugosity is to differentiate between corals and sand. A l l o f these data then w i l l be exported into ArcGIS for producing Digital Elevation Model (DEM) and make a results and analysis based on QPS Fledermaus model, BTM-Terrain Ruggedness (VRM) model and Coral Detection model. So, the result of this research shows on all three model which is profile detect the rugosity for the area to identify coral reefs. It is show the results given from QPS Fledermaus and Coral Detection of the accuracy is 55% similar o f coral representation, and also the BTM-Terrain Ruggedness (VRM) and Coral Detection of the accuracy is similar 51% o f coral representation. The total area covered by coral reefs based on QPS Fledermaus is 2685.208 m^ and for BTM-Terrain Ruggedness (VRM) is 15914.485 mf So that, the Coral Detection Model can identify more coral reefs area that covered is 19033.338 m^. As a conclusion. Coral Detection tool derived from Topographic Position Index can be used based on similar coral representation to detect coral reefs because the result of shape that show very dense and clear.